Stress - strain state mushroom caudal connections from the stiam turbaine blades - Фурсова, Татьяна Николаевна (Eastern-European Journal of Enterprise Technologies, 2014)
The distribution of strains in a two-point mushroom tail connection of a steam turbine blade is examined, and some results of the studies in this field are given in the paper. The main objective of the study lies in identifying and analyzing the VAT of a two-point mushroom tail connection by using experimental and computational methods for determining areas of the greatest risk due to the force and geometric strain concentration. The study of stress - strain state of a two-point mushroom tail connection within elastic deformations using the ANSYS software package has been carried out in the paper, and a comparison between the results of experimental and calculated data has been made. The zones, posing the greatest danger caused by the force and geometric strain concentration, have been determined. The research results can be used in turbine construction, when designing and exploiting steam turbines. It is proposed to apply the obtained results for preventing possible damages in the strain concentration zones.